“The devil looks ten times worse with a white face”: Colours in Richard Brome’s The English Moor - Cristina PARAVANO (E-REA)
This paper purposes to investigate the multiple meanings of the black and white opposition which lies at the basis of the plot of Richard Brome’s The English Moor. This binary can be seen as a contrast between Englishness and otherness as the oxymoronic title may suggest. In the play, the usurer Quicksands dresses up his own wife Millicent and other women as Moorish servants using black-face make-up. The way in which Brome uses black face as a theatrical device to vehicle a cultural ideology about otherness is new in terms of sexual politics, gender, cosmetics and race.The dualism which emerges in the plot is reflected in the use of space that I perceive as an opposition between the space of ‘white Englishness’ and that of ‘black otherness’: one of the locations chosen as a setting by Brome, the famous tavern of the Devil and St. Dunstan, contributes to reinforce the dichotomy that constitutes the play owing to its double reference to the devil, often associated with black, and to a saint. Moreover, the only scene set in the Devil Tavern occupies a strategic position in the middle of the play as a sort of watershed which divides white from black (after this scene Millicent and the other women wear black make-up) and recalls many issues developed in the previous scene such as Millicent’s transformation into a black Moor, the idea of otherness and a secret hidden in Quicksands’s past.What complicates the issue is that Brome does not in fact stage real otherness but uses the theatrical device of the disguise and of the black-white opposition to reproduce the prejudices of his contemporaries related to otherness.